The Role of Customer Experience in Mediating the Influence of Augmented Reality Marketing and Online Customer Reviews on Repurchase Intention of Wardah Products - Nasyihah, Dzurotul Khoir; Ponirin, Ponirin; Santi, Ira Nuriya; Farid, Farid (JURNAL MANAJEMEN MOTIVASI, 2025)
ABSTRACTThe purpose of this study was to determine the role of customer experience in mediating the influence of augmented reality marketing and online customer reviews on repurchase intention of Wardah products. This type of research uses explanatory research, by taking a quantitative approach, through distributing questionnaires as a data collection technique. In this study, the method used was purposive sampling technique. The method of data analysis and processing uses SEM-PLS analysis using Smart PLS 4.1 software. The findings of this study reveal that both Augmented Reality Marketing and Online Customer Review significantly have a positive effect on Customer Experience and Repurchase Intention of Wardah products, but Customer Experience is not proven to mediate the relationship between the two independent variables with Repurchase IntentionABSTRAKTujuan dari penelitian ini adalah untuk mengetahui peran customer experience dalam memediasi pengaruh augmented reality marketing dan online customer review terhadap repurchase intention Produk Wardah. Jenis penelitian ini menggunakan penelitian eksplanatif, dengan melakukan pendekatan kuantitatif, melalui penyebaran kuesioner sebagai teknik pengumpulan data. Dalam penelitian ini, metode yang digunakan adalah teknik purposive sampling. Metode analisis dan pengolahan data menggunakan analisis SEM-PLS dengan menggunakan software Smart PLS 4.1 Temuan penelitian ini mengungkapkan bahwa baik Augmented Reality Marketing maupun Online Customer Review secara signifikan berpengaruh positif terhadap Customer Experience dan Repurchase Intention produk Wardah, namun Customer Experience tidak terbukti memediasi hubungan antara kedua variabel independen tersebut dengan Repurchase Intention.